2019
DOI: 10.1088/1751-8121/ab0588
|View full text |Cite
|
Sign up to set email alerts
|

Hidden multiscale order in the primes

Abstract: We study the pair correlations between prime numbers in an interval M ≤ p ≤ M + L with M → ∞, L/M → β > 0. By analyzing the structure factor, we prove, conditionally on the Hardy-Littlewood conjecture on prime pairs, that the primes are characterized by unanticipated multiscale order. Specifically, their limiting structure factor is that of a union of an infinite number of periodic systems and is characterized by dense set of Dirac delta functions. Primes in dyadic intervals are the first examples of what we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 63 publications
(206 reference statements)
2
42
0
Order By: Relevance
“…Hence, the primes become effectively limit-periodic, despite the variable pattern of occupied sites, as proved in Ref. [27] and illustrated in Fig. 3.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Hence, the primes become effectively limit-periodic, despite the variable pattern of occupied sites, as proved in Ref. [27] and illustrated in Fig. 3.…”
Section: Resultsmentioning
confidence: 56%
“…The proof of (3) is given in Ref. [27]. It is based on grouping the terms in the sum defining S(πm/n) according to their remainder after division by 2n.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…† correspondence sent to: xwxfat@gmail.com ‡ correspondence sent to: mohanchen@pku.edu.cn § correspondence sent to: yang.jiao.2@asu.edu ¶ correspondence sent to: hzhuang7@asu.edu mune systems [27], amorphous silicon [28,29], a wide class of disordered cellular materials [30], dynamic random organizating systems [31][32][33][34][35], and even the distribution of primes on the number axis [36]. In addition, it has been shown that hyperuniform materials can be designed to possess superior physical properties including large isotropic photonic band gaps [37][38][39], optimized transport properties [40], mechanical properties [41] as well as optimal multi-functionalities [42].…”
mentioning
confidence: 99%